2023
DOI: 10.1038/s41598-023-33992-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and investigation of biological properties of silver nanoparticle-doped hydroxyapatite-based surfaces on zirconium

Abstract: The infections leading to failed implants can be controlled mainly by metal and metal oxide-based nanoparticles. In this work, the randomly distributed AgNPs-doped onto hydroxyapatite-based surfaces were produced on zirconium by micro arc oxidation (MAO) and electrochemical deposition processes. The surfaces were characterized by XRD, SEM, EDX mapping and EDX area and contact angle goniometer. AgNPs-doped MAO surfaces, which is beneficial for bone tissue growth exhibited hydrophilic behaviors. The bioactivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Any remedy for rendering antimicrobial properties to these surfaces is desired to present no systemic or localized toxicity, inhibit the proliferation of most species of microbial cells in contrast to a selected category of species, provide a robust system enabling ease-of-use, and involve a low production cost [5]. In this respect, silver coatings have been good candidates [6][7][8], thanks to their broad-spectrum antimicrobial activity through mechanisms such as production of reactive oxygen species (ROS) [9]. However, this approach is associated with drawbacks such as incompatibility of the conventional coating techniques with some important solids, altering the structure of surface, and corrosion with elution of silver ions, which ironically are the agent of antimicrobial activity [10].…”
Section: Introductionmentioning
confidence: 99%
“…Any remedy for rendering antimicrobial properties to these surfaces is desired to present no systemic or localized toxicity, inhibit the proliferation of most species of microbial cells in contrast to a selected category of species, provide a robust system enabling ease-of-use, and involve a low production cost [5]. In this respect, silver coatings have been good candidates [6][7][8], thanks to their broad-spectrum antimicrobial activity through mechanisms such as production of reactive oxygen species (ROS) [9]. However, this approach is associated with drawbacks such as incompatibility of the conventional coating techniques with some important solids, altering the structure of surface, and corrosion with elution of silver ions, which ironically are the agent of antimicrobial activity [10].…”
Section: Introductionmentioning
confidence: 99%
“…According to Hassan et al, a huge amount (75%) of postimplant infections are caused by bacterial infections, especially Staphylococcus aureus, which colonize over time to form biofilm, finally resulting in uncurable disease and early failure of the implant. Recent studies showed that the utilization of silver (Ag) as an antibacterial agent improves remodeling by inhibiting infection through damaging cell walls or intracellular organisms (DNA and protein) by attaching Ag + ions to the bacterial cell wall by electrostatic forces. Bee et al synthesized AgNP (AgNO 3 ∼1, 3, and 5 wt %)-decorated HA-based biocomposites, where HA was extracted from chicken bones, and the results showed that AgNO 3 concentration used >1 wt % possessed higher bioactivity in Hank’s balanced salt solution. In another study, Afzal et al reinforced the HA with 5 wt % Ag and sintered at 950 °C using spark plasma sintering to form the cylindrical pellets, and the result showed an increment in the hardness and elastic modulus by 15 and 5%, respectively, with effective antibacterial properties by reducing bacterial adhesion by 64.9% for Escherichia coli and 78.8% for Staphylococcus epidermidis.…”
Section: Introductionmentioning
confidence: 99%
“…The post-implantation infections are of prime importance since they put additional health and economic burden on the patient. Thus, it is better to use a reinforcing phase that can enhance the antibacterial performance of the pure HAp even if the obtained improvement is not too significant 20 23 .…”
Section: Introductionmentioning
confidence: 99%